W.E. Sheridan Louis the Eleventh - Morgan, Matthew Somerville, 1839-1890.; Ledger Job Printing Office (Philadelphia, Pa.) (Phil. : Ledger Job Print, [ca. 1880])
Image depicts full-length figure of W.E. Sheridan as Louis the Eleventh.
Forms part of the Theater Poster Collection; for general information, see collection record.
Letterpress reads: Chestnut/Farewell/Engagement./. . ./March 15 & 16/. . .
Provenance unknown.
Keywords: Drama -- Pennsylvania -- Philadelphia